John Hicks. The crisis in Keynesian economics. Oxford : Basil Blackwell, 1974. 85 p. - Méndez Villarreal, Sofía (Estudios Demográficos y Urbanos, 1975)
JOHN HICKS, The Crisis in Keynesian Economics, Oxford, Basil Blackwell, 1974.